2022
DOI: 10.3389/fpsyg.2022.1038878
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and grit in English as a foreign language learning among high school students: A three-wave longitudinal study

Abstract: This study examined the longitudinal reciprocal relations between students’ grit and their perceptions of social relationships (teacher-student and peer relationships) in studying English as a foreign language (EFL). A total of 2,435 students from Grades 10-11 in China (Mage = 16.40 years old, 54.2% female) participated in the study on three occasions across 1 year. The three-wave cross-lagged analytic model results indicated that (a) peer relationship and grit reciprocally enhanced each other across both inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Lam and Zhou (2022) examined the relations between grit and academic achievement based on a meta-analysis of 137 studies and found that the correlations of overall grit level with academic achievement were generally weak to moderate. Empirical studies explored the domainspecific versus general aspects of grit in educational contexts (e.g., Schmidt et al, 2017) which consistently showed that domain-specific grit is a better predictor of achievement than general grit (Cui & Yang, 2022). TA B L E 3 (Continued)…”
Section: Discussionmentioning
confidence: 99%
“…Lam and Zhou (2022) examined the relations between grit and academic achievement based on a meta-analysis of 137 studies and found that the correlations of overall grit level with academic achievement were generally weak to moderate. Empirical studies explored the domainspecific versus general aspects of grit in educational contexts (e.g., Schmidt et al, 2017) which consistently showed that domain-specific grit is a better predictor of achievement than general grit (Cui & Yang, 2022). TA B L E 3 (Continued)…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies drew participants from various countries or regions, including South Korea (N=4), Taiwan (N=4), the United States (N=4), Saudi Arabia (N=4), Turkey (N=3), Hong Kong SAR (N=2), Indonesia (N=2), Japan (N=2), Spain (N=2), Ethiopia (N=1), Iraq (N=1), Kuwait (N=1), Norway (N=1), Poland (N=1), and Russia (N=1). Five studies explored cross-cultural groups, such as the study by Yang et al (2022) [18] which included participants from the Chinese mainland and Iran, and Sudina et al (2021b) [19] which involved 104 ESL learners from Canada, Japan, South Korea, and the United States, as well as 350 EFL learners. In terms of sample sizes, the studies varied significantly, ranging from 30 to 3272 participants.…”
Section: Samplingmentioning
confidence: 99%
“…In another study, [38] and Cui and Yang (2022) [40] adopted a longitudinal design, allowing for the evaluation of the scale's validity over time. Their results indicated that the fit indices of the measurement models were satisfactory and that the latent factor of L2 grit remained invariant across time.…”
Section: Scale Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that in mathematics learning, the fortitude of female and male students did not differ significantly (Flanagan & Einarson, 2017). Another opinion states that the level of grit of female and male students does not have a significant difference (bin Shariff et al, 2022;Cui & Yang, 2022;Guo et al, 2023;Hodge et al, 2018). Although females have lower grit than males, the difference is insignificant (Bennett et al, 2021).…”
Section: Hypothesis Verificationmentioning
confidence: 99%